Biological Hydrogen Production: Not so Elementary - Michael W. W. Adams; Stiefel, Edward I. (Science (American Association for the Advancement of Science), 1998)
Peters et al report their usage of x-ray crystallography to provide the first structural glimpse of the iron-only hydrogenase from the hydrogen-producing, anaerobic bacterium Clostridium pasteurianum.